A landscape of two linguistic worlds and its investigation using a clustering method: a contribution to the possibilities of DBSCAN in archaeological-linguistic research - Janovský, Martin; Jansens, Nicolas; Janovská, Viktorie; Klír, Tomáš (Journal of European landscapes, 2024)
Abstract At the intersection of historical and linguistic sciences, a digital method is tested here using data from the region of Bavaria (Germany) where significant Slavic settlement existed during the early Middle Ages. This contact zone, so-called Bavaria Slavica, is a suitable area in which to use our knowledge of toponomastics, settlement history, and archaeology to test modern tools of spatial analysis. One of these tools is DBSCAN, with the potential to differentiate data clusters corresponding to old settlement cores in Bavaria. While it is important to assess the presence or absence of certain types of place names in a given space, their quantitative density is also an important reflex of settlement patterns. Our key finding is that the area of Bavaria in which the Slavic-speaking population enjoyed its greatest prosperity was in a region contemporaneously inhabited by Germans, with whom they interacted. Hence, this study substantiates the idea that mediaeval north-eastern Bavaria was a contact zone characterized by the intermingling of languages and cultures.